Redução de dose em varreduras de tomografia computadorizada de tórax - otimização de protocolos utilizando objetos simuladores adultos e pediátricos - Wadia Namen Aburjaile (2021)
Computed tomography (CT) images are very detailed and used for medical diagnosis, being considered relevant in ionizing radiation applications. Due to the continuous increase in the demand for these tests, CT has become the diagnostic procedure that most contributes to the increase in the dose absorbed by the population. The optimization of the image acquisition process aimed at reducing the dose in patients and maintaining the diagnostic quality of the image has become an object of research in recent years, mainly in pediatric applications. For this work, Iive human chest phantoms representing different volumes of patients were made, one in cylindrical shape and the other four oblong, two for adult and three for pediatric patients. The objects are made of polymethylmethacrylate and have openings that allow the measurement of absorbed dose values using a pencil-type ionization chamber. The CT scans of the phantoms were performed on two devices using different acquisition protocols, always starting from the routine chest protocol used by the diagnostic service. The tested protocols used different voltage values (80, 100, 120, 135 and 140 kV) and from the test results, the best acquisition protocol was deIined for each phantom in each CT device. The absorbed dose values recorded using the optimized protocols generated considerably lower doses in patient than those received with the routine protocol. In order to maintain the diagnostic quality of the image, an analysis of the noise generated in the image of the central slice was made. The noise value was kept below 1%. This noise index value is considered very good for homogeneous materials, such as phantoms. The new optimized protocols were implemented and used in patient scans and allowed to generate images with very good diagnostic quality.